1995
DOI: 10.1897/1552-8618(1995)14[713:iopott]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF pH ON THE TOXICITY OF AMMONIA TO CHIRONOMUS TENTANS AND LUMBRICULUS VARIEGATUS

Abstract: The U.S. Environmental Protection Agency water-quality criteria establish permissible levels of ammonia in the nation's fresh waters. These criteria are based on accumulated research suggesting that, for most aquatic species (primarily fishes), the toxicity of un-ionized ammonia predominates over that of the ammonium ion. The development of a sediment-quality criterion for ammonia requires evaluation of the relative toxicity of the two ammonia forms to benthic and epibenthic macroinvertebrates to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 8 publications
4
60
0
1
Order By: Relevance
“…Ca-poor environments could be limiting for snail eggshell formation and skeletal growth in nestlings, and during the reproduction period, snails usually concentrate on Ca-high zones (Tipping et al 2002, Scheuhammer et al 1997, Graveland et al 1994, Schubauer-Berigan et al 1995. Compared to oligochaetes and insects, mollusks may be more acid-sensitive, since Ca concentration is negatively related to acidification (Scheuhammer et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Ca-poor environments could be limiting for snail eggshell formation and skeletal growth in nestlings, and during the reproduction period, snails usually concentrate on Ca-high zones (Tipping et al 2002, Scheuhammer et al 1997, Graveland et al 1994, Schubauer-Berigan et al 1995. Compared to oligochaetes and insects, mollusks may be more acid-sensitive, since Ca concentration is negatively related to acidification (Scheuhammer et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…EROD and AHH were low and could not differentiate between pharmaceutical waste water before and after treatment (P-IF and P-EF). The waste water treatment reduced N-toxicity for prawn by creating slightly alkaline conditions, which resulted in a shift from NH 3 to less toxic NH þ 4 (Burkhard and Jenson, 1993;Schubauer-Berigan et al, 1995). The effluent contained up to 10.9 mg l À1 nitrite.…”
Section: Pharmaceutical Waste Watermentioning
confidence: 99%
“…lower pHs Walker et al, 1996 . However, empirical studies have indicated toxicity changes are often metal Ž and organism dependent Campbell and Stokes, 1985;Schubauer-Berigan et al, 1993;Sandifer and Hopkin, . 1996;Walker et al, 1996;Cuismano et al, 1986.…”
Section: In This Series Of Tests Ic50 Values For Metals With Mmentioning
confidence: 99%
“…Metal toxicity is often dependent upon pH in freshwa-Ž ter and soils Campbell and Stokes, 1985;Schubauer-. Berigan et al, 1993;Sandifer and Hopkin, 1996 .…”
Section: Introductionmentioning
confidence: 99%